2021
DOI: 10.3390/ijms22189907
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Suppresses Oral Squamous Cell Carcinomas Migration and Invasion through Blocking FGF19/FGFR 4 Signaling Pathway

Abstract: Oral squamous cell carcinomas (OSCCs) are one of the most prevalent malignancies, with a low five-year survival rate, thus warranting more effective drugs or therapy to improve treatment outcomes. Melatonin has been demonstrated to exhibit oncostatic effects. In this study, we explored the anti-cancer effects of melatonin on OSCCs and the underlying mechanisms. A human tongue squamous cell carcinoma cell line (SCC-15) was treated with 2 mM melatonin, followed by transwell migration and invasion assays. Relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Lastly, melatonin abolishes the invasion and migration abilities of SCC-15 cells while decreasing Fibroblast Growth Factor 19 (FGF19) in oral squamous carcinoma cells (SCC-15). The addition of exogenous hFGF19 appears to revoke the effect of the indolamine on cell invasion and migration, whereas FGF19 knockdown mimics the effect of the melatonin treatment [ 170 ].…”
Section: Melatonin As An Inhibitor Of the Epithelial-to-mesenchymal T...mentioning
confidence: 99%
“…Lastly, melatonin abolishes the invasion and migration abilities of SCC-15 cells while decreasing Fibroblast Growth Factor 19 (FGF19) in oral squamous carcinoma cells (SCC-15). The addition of exogenous hFGF19 appears to revoke the effect of the indolamine on cell invasion and migration, whereas FGF19 knockdown mimics the effect of the melatonin treatment [ 170 ].…”
Section: Melatonin As An Inhibitor Of the Epithelial-to-mesenchymal T...mentioning
confidence: 99%
“…In the tumor progression phase, the growth and invasion of tumor cells increase rapidly. Melatonin could inhibit cancer cell growth and downregulate matrix metallopeptidase 9 (MMP-9) [ 34 ] and fibroblast growth factor 19 (FGF19) [ 35 ] to inhibit cancer cells’ invasion and migration. Moreover, in vivo studies have demonstrated that melatonin alleviates cancer progression by inactivating Notch homolog 1 (Notch 1) receptor [ 36 ], suppressing estrogen/ubiquitin C/SDHB-mediated succinate accumulation [ 37 ], inhibiting MMP-13 [ 38 ], and downregulating receptor activator of nuclear factor kappa-Β ligand (RANKL) expression levels [ 39 ].…”
Section: Anticancer Effect Of Melatoninmentioning
confidence: 99%